2013
DOI: 10.1007/s00484-013-0712-5
|View full text |Cite|
|
Sign up to set email alerts
|

Inter-animal radiation as potential heat stressor in lying animals

Abstract: A model for predicting inter-animal radiant heat exchange in shaded animals is presented, with emphasis on mature cattle. When a cow's surface temperature is 35 °C, as is common in warmer climates, it loses ∼510 Watt m(-2) as radiant heat. Net radiant heat balance depends on radiation coming from bodies in the vicinity. In the 30 °C radiant temperature shaded environment typical of warm climates, net radiant loss from a lactating cow is ∼60 Watt m(-2), i.e., 30 % of its ∼173 Watt m(-2) heat production. Cows re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Another study observed a maximal rate of water loss due to evaporative cooling in 600 kg lactating dairy cows of 1.5 kg h −1 6 . Using an estimate of surface area for such a cow of 6.54 m 2 , that value of 1.5 kg h −1 implies maximal sweating at only 230 ml m −2 h −1 , which is quite a bit lower than that reported by Berman 39 . When Bos indicus and Bos taurus heifers of similar body mass (335 kg) were placed into a climate chamber and exposed to the same, gradually rising, ambient temperature and humidity, the core temperature of the Bos indicus did not increase significantly until the wet‐bulb temperature exceeded 30°C, while the core temperature of the Bos taurus increased 4 days earlier, when the wet‐bulb temperature was 26°C 30 .…”
Section: Thermoregulationmentioning
confidence: 78%
See 2 more Smart Citations
“…Another study observed a maximal rate of water loss due to evaporative cooling in 600 kg lactating dairy cows of 1.5 kg h −1 6 . Using an estimate of surface area for such a cow of 6.54 m 2 , that value of 1.5 kg h −1 implies maximal sweating at only 230 ml m −2 h −1 , which is quite a bit lower than that reported by Berman 39 . When Bos indicus and Bos taurus heifers of similar body mass (335 kg) were placed into a climate chamber and exposed to the same, gradually rising, ambient temperature and humidity, the core temperature of the Bos indicus did not increase significantly until the wet‐bulb temperature exceeded 30°C, while the core temperature of the Bos taurus increased 4 days earlier, when the wet‐bulb temperature was 26°C 30 .…”
Section: Thermoregulationmentioning
confidence: 78%
“…A lactating dairy cow with a skin temperature of 36 C will radiate around 500 W m À2 , equating to 3.27 kW for a 600 kg cow, which is about one-third of their metabolic heat production. 39 Because radiant exchange occurs between any two surfaces that "see" each other, heat is transferred between animals by radiation. Thus, stock density impacts the distance between animals and subsequently the rate of between-animal radiant heat transfer.…”
Section: Heat Sources and Sinksmentioning
confidence: 99%
See 1 more Smart Citation